The Internet as an information conduit in developing countries : an investigation of World Wide Web usability among small and medium textile enterprises in Botswana - Cronje, Johannes Christoffel (University of Pretoria, 2013)
Thesis (DPhil (Information Science))--University of Pretoria, 2007.